8w+6=-2(w-7)

Simple and best practice solution for 8w+6=-2(w-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8w+6=-2(w-7) equation:


Simplifying
8w + 6 = -2(w + -7)

Reorder the terms:
6 + 8w = -2(w + -7)

Reorder the terms:
6 + 8w = -2(-7 + w)
6 + 8w = (-7 * -2 + w * -2)
6 + 8w = (14 + -2w)

Solving
6 + 8w = 14 + -2w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '2w' to each side of the equation.
6 + 8w + 2w = 14 + -2w + 2w

Combine like terms: 8w + 2w = 10w
6 + 10w = 14 + -2w + 2w

Combine like terms: -2w + 2w = 0
6 + 10w = 14 + 0
6 + 10w = 14

Add '-6' to each side of the equation.
6 + -6 + 10w = 14 + -6

Combine like terms: 6 + -6 = 0
0 + 10w = 14 + -6
10w = 14 + -6

Combine like terms: 14 + -6 = 8
10w = 8

Divide each side by '10'.
w = 0.8

Simplifying
w = 0.8

See similar equations:

| lx+3l=3x+6 | | 3(x+5)-2x=15 | | 6x-77+2x=43 | | -16/9=-8u | | 7x-2(1+3x)=2 | | 18+5w=3w-10 | | 5y-3/5=4/3 | | -(3v+4)=6v-3(3v+2) | | 77+4x=43 | | -2x(3x+4)+y=0 | | 0+1x=0.2(x+2) | | 3W-6+6W=-2+W | | -2/3t=6 | | 5x-x=12+6x | | 9w-2=-1w-22 | | -x-40+4x=26 | | 7v/6=-35 | | 4(x-5)+4(x-5)+3(x+6)+3(x+6)= | | 8y+9y-y-4+1y-4y=36 | | 5n-7=5(n+2)+3 | | A=pt-3p | | 1/2-3=9 | | 9(8-12w)= | | 5(x-3)=-(15-5x) | | -68+4x+3x=114 | | 5x/2=-3x+11 | | 5p-2(4-2p)=19 | | Y=-2+-0.6666666667x | | -3/7w=9 | | 2x-(2-x)=13 | | x=(2m-4)/(1+n) | | 125^-2/3 |

Equations solver categories